Role of Internet of Things (IoT) in Maximum Power Extraction from BIPV Modules: A Review for Developing Smart Zero Energy Buildings - Sarkar, Debayan; Shukla, Apoorva; Kumar, Anand; Kumar Sadhu, Pradip (International Journal of Engineering and Technology, 2018)
Evolution of Building Integrated Photovoltaic's (BIPV) technology has resulted in the development of smart buildings as a clean source of electrical energy generation which can either be stand alone or grid connected systems. This paper briefs about the studies on the role of Internet of Things (IoT) in real-time controlling and monitoring of parameters like tilt angles, defected modules, shading effect in BIPV systems etc which decreases the dc power output. In addition, it also describes the use of IoT for maximum power extraction from BIPV modules present in rooftops and facades. Enabling IoT in BIPV installation makes the overall system cost-effective, energy efficient, reliable and can be operated remotely through android apps, smart phones, laptops, PCs, tablets etc via internet which is very easily accessible in recent times. IoT along with BIPV is showing a new direction towards smart generation from renewable energy resources like solar through PV integrated building or construction materials.Â Â